Pentingnya Nilai-Nilai Agama Hindu Di Era Globalisasi - Gusti Nyoman Wiradnyana; Putu Agustiantini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Religion is a system that regulates belief and worship of God (or the like) as well as rules related to culture, and worldviews that connect humans with the order of life. Many religions have mythologies, symbols, and sacred histories intended to explain the meaning of life and the origin of life or the universe. From their beliefs about the cosmos and human nature, people derive their morality, ethics, religious law, or lifestyle of their choice. According to some estimates, there are about 4,200 religions in the world. Many religions may have regulated conduct, the priesthood, defined what constitutes obedience or membership, holy places, and scriptures. Religious practices may also include rituals, sermons, memorials or worship of gods, gods or goddesses, sacrifices, festivals, feasts, trances, initiations, funerals, weddings, meditation, prayer, music, art, dance, or other aspects of human culture. Religion may also contain mythology. The word religion is sometimes used interchangeably with faith, belief system, or sometimes to set a task. The definition of religion here is as simple and comprehensive as possible. This definition is expected not too narrow and not too loose, but can be applied to religions that have been known through the mention of the names of these religions. Religion is an institution or institution that regulates human spiritual life. For this reason, regarding what is called religion, it is necessary to find points of similarities and points of difference.